Pediatric Orbital Depth and Growth. Issue 6 (September 2015) - Chang, Johnny T.; Morrison, Clinton S.; Styczynski, John R.; Mehan, William; Sullivan, Stephen R.; Taylor, Helena O.
<x xml:space="preserve">Abstract</x> Background: Orbital reconstruction requires knowledge of orbital depth in order to prevent optic nerve injury. Numerous analyses of adult orbital dimensions have been undertaken previously in order to characterize this measurement, including skull specimen and computerized tomography studies. However, there is a paucity of information regarding the pediatric orbit. Methods: The authors used pediatric magnetic resonance imaging (MRI) studies in order to quantify the change in orbital depth in relationship to patient age, and to develop methods to estimate and calculate orbital depth for individual pediatric patients. MRIs of the head in normal pediatric patients were reviewed retrospectively. Orbital depths were measured and correlated with age and cephalometric dimensions. In a randomly selected subgroup of patients, measurements were repeated by an independent investigator to determine interobserver reliability. Results: Measurements were obtained in 72 patients ranging from 3 months to 18 years of age (mean = 7.8 years). There was a significant exponential relationship between orbital depth and patient age (r2 = 0.81, F(2, 69) = 143.97, P < 0.001). Depth increased more rapidly in the first 6 years of life, but leveled off in the early teen years toward a horizontal asymptote of approximately 45 mm. There was also a significant relationship between orbital depth and the sum of the biparietal width plus the anterior–posterior length (r2 = 0.72, F(2, 69) = 87.44, P < 0.0001). There was high interobserver reliability in measurements between 2 independent investigators (r = 0.79, P < 0.0001). Conclusion: In children, orbital depth increases predictably with rising age and increasing head size. Knowledge of this growth curve and the relationship between head size and orbital depth can complement careful surgical dissection to improve safety and efficacy in pediatric orbital reconstructions.